Escola de tempo integral e currículo: desafios e perspectivas do núcleo gestor sobre o Programa do Sistema Municipal de Educação de Mogi das Cruzes SP, no período de 2009 a 2013 - Santos, Juliana de Paula Guedes de Melo (2014)
The setting of this research are the Schools Full Time , Primary Education , the Municipal Education System in the city of Mogi das Cruzes - SP , during the years 2009 to 2013. The structuring and consolidation of this school model emerged in response to broader social issues involving risk and vulnerability that are exposed schoolchildren . However , the organizational complexity of both teaching , as administrative , restructuring and consolidation required for this proposed school emphasizes problem investigated here are the challenges and prospects of the core members of the manager about his own work and curricular issues related to School Time integral . The central objective is guided to identify the perceptions of members of the core manager issues related to the prescribed curriculum and the lived curriculum , this post considering time, space , text and context. Data collection was conducted from questionnaires completed by members of the Center Manager - director , deputy director and educational coordinator - Four Schools Full Time , located in one of the districts of the city . This cut was chosen by the multiplicity of characteristics of schools that are ( number of students per school, type of building construction and date of inclusion in School Full Time Program of the municipality ) , and thus depict the differences found within each school units and justify the complexity of the work of the Center Manager of each of the schools. The results were analyzed in light of the theories of several authors and is intended to constitute up major collaborative reflection of the structure and organization of these schools elements , since the announced expansion of the program in the city of Mogi das Cruzes - SP , government city for the next year as a way to fulfill the National Education Plan